Regional alterations of repolarizing K(+) currents among the left ventricular free wall of rats with ascending aortic stenosis - Volk, Tilmann (Blackwell Science Inc, 2001)
1. The effect of cardiac hypertrophy on electrocardiogram (ECG), action potential duration (APD) and repolarizing K(+) currents was investigated in epicardial, midmyocardial and endocardial myocytes isolated from the rat left ventricular free wall. 2. Cardiac hypertrophy was induced by stenosis of the ascending aorta (AS), which led to an increased pressure load (+85 ± 10 mm) of the left ventricle; sham-operated animals served as controls. 3. In ECG recordings from AS rats, the QTc interval was prolonged and the main vectors of the QRS complex and the T-wave pointed in opposite directions, indicating an abnormal sequence of repolarization. 4. APD and K(+) currents were recorded using the whole-cell patch-clamp technique. In the AS group, APD(90) (90 % repolarization) was significantly prolonged in epicardial and midmyocardial, but not endocardial myocytes. 5. Corresponding to the increase in APD, the magnitude of the transient outward K(+) current (I(to1)) was significantly smaller (-30 %) in epicardial and midmyocardial, but not endocardial myocytes. 6. Inactivation and steady-state inactivation of I(to1) were not affected by hypertrophy. Recovery from inactivation was slightly prolonged in endocardial myocytes from AS rats. 7. No differences in delayed rectifier currents (I(K)) or inwardly rectifying K(+) currents (I(K1)) were detected between myocytes of the three regions of sham-operated or AS animals. However, both currents were reduced by AS. 8. The present data show that cardiac hypertrophy caused by pressure overload leads to an increase in APD and a decrease in I(to1) primarily in epicardial and midmyocardial myocytes, which implies a major role of alterations in I(to1) for the reduced gradient in APD. The effects of AS on I(K1) and I(K) may slightly counteract the decrease in APD gradient. The observed changes in APD and underlying ionic currents could well explain the alterations in repolarization observed in the ECG induced by cardiac hypertrophy.